Effect of nutrient sources on growth and yield performance of mung bean (Vigna radiata L.) in western Terai, Nepal - Khanal, Ram Prasad; Dahal, Khem Raj; Amgain, Lal Prasad; Neupane, Samir; Adhikari, Nirjala; Gautam, Ishan; Ghimire, Prakash (Frontiers in Agronomy, 2025)
Mung bean (Vigna radiata L.) is a multipurpose pulse crop, mostly cultivated as a catch crop in fallow land during the spring season between wheat and rice crops. An experiment entitled “Effect of nutrient sources on growth and yield performance of mung bean at western terai, Nepal” was conducted at the Agronomy Research Farm of Paklihawa Campus during April to July 2023 to improve the production of mung bean with the application of organic and inorganic nutrient sources. The field was laid out in a Randomized Complete Block Design with 8 treatments and 4 replications. Treatment structure consists of Control, Recommended Doses of Nitrogen (RDN) from Prilled Urea (PU), RDN + 25% from PU, RDN-25% from PU, RDN from Farm yard manure, RDN from Poultry manure, Nano urea, and Rhizobium inoculation. Results shows that poultry manure applied plots exhibited better growth and yield performance with higher shoot length (85.54cm), number of leaf plant-1 (13.72), leaf area index (2.26), crop growth rate (0.9910 g day-1), average number of branches plant-1 (2.9), number of pods plant-1 (22.38), pod length (8.08cm), average number of seeds pod-1 (7.22), thousand seeds weight (57.40 g), seed yield (1028 Kg ha-1), stalk yield (1650 Kg ha-1), biological yield (2678 Kg ha-1) and harvest index (38.38%) followed by Farm yard manure (FYM). FYM applied plots had better root length (23.66cm) and number of nodules (13.05). Organic nutrient application is better for short-duration crops like mung beans. Growth and yield increased with an increase in the dose of prilled urea, and hence, the actual yield of mung beans can be increased by increasing the dose of prilled urea above the government recommendation. For precise recommendations in a larger domain, a multi-seasonal and multi-location research is suggested.